Incidence and risk factors of symptomatic knee osteoarthritis among the Chinese population: analysis from a nationwide longitudinal study - Yan Ren; Jiang Hu; Jing Tan; Xiaoming Tang; Qianrui Li; Huazhen Yang; Chunrong Liu; Qiao He; Kang Zou; Xin Sun; Bo Tan (BMC, 2020)
Abstract Background Knee osteoarthritis (OA) is a common disease condition associated with aging and a frequent cause of primary care consultations. Few longitudinal studies have been conducted to investigate the incidence of symptomatic knee osteoarthritis (OA) and to identify its risk factors among the Chinese population. Methods The China Health and Retirement Longitudinal Study (CHARLS) is a nationwide longitudinal survey of persons aged ≥45 years. Symptomatic knee OA was diagnosed when both self-reported knee pain and self-reported physician-diagnosis arthritis existed. Using the national survey data collected from the CHARLS, we estimated the incidence of symptomatic knee OA, taking into account the complex survey design and response rate. We applied weighted logistic regression analysis to identify its risk factors. Results In the 4-year follow-up, the cumulative incidence of symptomatic knee OA among middle-aged and older Chinese adults was 8.5%; the incidence was higher among females (11.2%) than males (5.6%). Female (odds ratio (OR) 1.98 [95% confidence interval (CI) 1.65-2.37]), rural area (OR 1.32 [95% CI 1.08-1.60]), and West region (OR 2.33 [95% CI 1.89-2.87]) were associated with a higher risk of incident symptomatic knee OA. Physical activities (OR 0.47 [95% CI 0.29-0.76]) and high education level (OR 0.60 [95% CI 0.41-0.88]) was associated with a lower risk of incident symptomatic knee OA, while histories of heart disease (OR 1.40 [95% CI 1.07-1.82]), kidney disease (OR 1.80 [95% CI 1.35-2.39]), and digestive disease (OR 1.54 [95% CI 1.30-1.82]) were associated with a higher risk of incident symptomatic knee OA. Conclusion The cumulative incidence of symptomatic knee OA over 4 years was relatively high, and varied by province and region. Lack of physical activities was confirmed to be risk factors of incident symptomatic knee OA. The presence of heart disease, kidney disease, and digestive disease may be associated with a higher risk of incident symptomatic knee OA, further research need to confirm these findings.